Sources of PM2.5 exposure and health benefits of clean air actions in Shanghai - Yixuan Gu; Daven K. Henze; Hong Liao (Environment International)
Estimating PM2.5 exposure and its health impacts in cities involves large uncertainty due to the limitations of model resolutions. Consequently, attributing the sources of PM2.5-related health impacts at the city level remains challenging. We characterize the health impacts associated with chronic PM2.5 exposure and anthropogenic emissions in Shanghai using a chemical transport model (GEOS-Chem) and its adjoint. By incorporating high-resolution satellited-derived PM2.5 estimates into the calculation, we investigate the response of PM2.5 exposure and its related health impacts in Shanghai to changes in anthropogenic emissions from each individual region, species, sector, and month. We estimate that a 10% decrease in anthropogenic emissions throughout China avoids over 752 (506–1,044) PM2.5-related premature deaths in Shanghai, with changes in local emissions potentially saving 241 (161–334) lives. Ammonia (NH3) emissions are identified as the marginal dominant contributor to the health impacts due to the NH3-limited PM2.5 formation within the city, thus controlling NH3 emissions at both the local and regional scales are effective at reducing the population’s exposure to PM2.5. A negative response of the PM2.5 exposure to local nitrogen oxides (NOx) emission changes is detected in winter. Even so, controlling NOx emissions is still justified since the negative impacts decrease as anthropogenic emissions decline and NOx emission reductions benefit the public health on average. The anthropogenic emission changes due to Clean Air Actions helped avoid 3,132 (2,108–4,346) PM2.5-related premature deaths in 2019 relative to 2013, most of which are associated with emission reductions in the agricultural and industrial sectors.